The influence of communication platform on the students' engagement in the magnetic electricity e-learning class. (February 2020) - Liani, N S; Nur, S; Huda, I
Abstract: This study aims to determine the effect of the communication platform on student involvement in learning electronic magnetic electricity. This study uses a quasi-experimental method with experiment, control group, and use only posttest control group design. Random sampling techniques used on 72 students of class 2017/2018 Physics Education courses who studied magnet electricity subject and all divided into three classes. One is the experimental class, and two are the control group classes. The results indicated that the t-score was 0.76 therefore, the ttable in the significant level of α = 0.05 which is 1.99 so that 0.76 < 1.99. As a result, Ho is accepted, and Ha rejected. As a conclusion, the communication platform does not have a significant effect on the students' involvement.